Macroalgae ecosystem engineering effects mediated by an invasive reef-builder polychaete in a Southwestern Atlantic coastal lagoon - Bazterrica, Maria Cielo (2021)
Macroalgae in Mar Chiquita coastal lagoon (37◦ 40′ S, 57◦ 23′ W, Argentina) settle on small-hard substrates on sediments and complex reef-like structures with tubes and crevices of the invader polychaete Ficopomatus enigmaticus (Fauvel, 1923) acting as ecosystem engineers with multiple community structuring effects. In this study, we compared the structural effects of macroalgae generating new habitat for other organisms in two systems with originally different structural complexity. Therefore, we hypothesized that macroalgae relative importance as an ecosystem engineer providing new habitat and refuge for other organisms would be higher in flat soft-sediments than on reefs. Through sampling and experimental studies, results showed that macrofaunal assemblages were different between areas with and without macroalgae in both reefs and sediment. Experimental results on macroalgae and macroalgae-mimics to separate structural effects in both reefs and sediment showed that macroalgae affect macrofauna on both systems but, structural mechanisms did not prevail in the reefs or sediment. The effect varied on species responses and physical gradients (i.e., depth) of each type of area. Therefore, our results did not support our hypothesis and suggest that macroalgae effects are the result of a summary of their multiple effects in interaction with species and habitat type.